2014
DOI: 10.1103/physrevlett.113.218701
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Difference Scheme for Large Scale Scientific Simulations

Abstract: We argue that the current heterogeneous computing environment mimics a complex nonlinear system which needs to borrow the concept of time-scale separation and the delayed difference approach from statistical mechanics and nonlinear dynamics. We show that by replacing the usual difference equations approach by a delayed difference equations approach, the sequential fraction of many scientific computing algorithms can be substantially reduced. We also provide a comprehensive theoretical analysis to establish tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…It clearly shows the delay error from the proxy-equation approach is much smother and also lower in magnitude. Similar observations can be made when comparing the delayed time difference scheme [9] with the proxy-equation approach , FIG. 5(b).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…It clearly shows the delay error from the proxy-equation approach is much smother and also lower in magnitude. Similar observations can be made when comparing the delayed time difference scheme [9] with the proxy-equation approach , FIG. 5(b).…”
supporting
confidence: 73%
“…Currently a few numerical schemes have been developed to improve the accuracy of asynchronous computations. Recently developed asynchrony-tolerant numerical scheme [8] and the delayed difference scheme [9] attempt to counteract the delay error due to asynchrony by modifying the discretization scheme. However, the delay error still continues to be significant.…”
mentioning
confidence: 99%
“…Thus, schemes with delay on both sides will need a smaller stencil to compute derivatives. In [12], this approach was used to recover the drop in accuracy due to delay in communication in a particular application using central difference schemes. The authors further suggested that imposing delay on both sides of the stencil in central differences would suffice to maintain the accuracy under asynchronous conditions.…”
Section: Alternative Approachmentioning
confidence: 99%
“…They also proposed the possibility of deriving schemes that are tolerant to communication data asynchrony. A follow up of this work to a simple specific equation and numerical scheme has be presented in [12]. Although the authors were able to maintain second order accuracy for their chosen scheme when asynchrony is present, one can show using Taylor series that they are severely limited to low order of accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome this bottleneck, some work has focused on relaxing the synchronization requirements among the processors and perform so-called asynchronous numerical simulations. Early work in the literature dealt with asynchronous simulations but severely limited to lower orders of accuracy and restricted to certain class of PDEs [19,20,21,22]. A new and more generalized approach, extensible to arbitrarily high orders of accuracy, has been recently developed [23,24] to derive the so-called Asynchrony-Tolerant (AT) finite-difference schemes.…”
Section: Introductionmentioning
confidence: 99%